Penerapan Media Papan Monopoli Kuis Pokok Bahasan Zat Adiktif Kelas VIII SMP untuk Meningkatkan Hasil Belajar Siswa - Jayanti Kusumastuti; Mohammad Budiyanto, (Indonesian Journal of Science Learning (IJSL), 2022)
This study aimed to describe the improvement of students' learning outcomes by implementing monopoly quiz board media on the subject of addictive substances. This study was a pre-experimental with one group pretest-posttest design. This study involved 32 students of class VIII-G in one of the public Junior High Schools in Gresik. Data collection techniques used were observation, written tests, and surveys. The implementation of learning at the first and second meetings was considered very good. Learning outcomes were analyzed using N-gain, which showed the medium category. The results of the students' responses questionnaire received positive responses to the implementation of the monopoly quiz board media. Based on the results, it can be concluded that the implementation of the monopoly quiz board media improved students' learning outcomes on the subject of addictive substances.